Gold Nanoparticles Enhance EGFR Inhibition and Irradiation Effects in Head and Neck Squamous Carcinoma Cells - Akashi, Masaya; Fukuoka, Takao; Yamaguchi, Akinobu; Hasegawa, Takumi; Teraoka, Shun; Kakei, Yasumasa; Kashin, Masahiko; Sasaki, Ryohei (BioMed research international, 2020)
Cetuximab, an epidermal growth factor receptor inhibitor (EI), is currently the only targeted molecular therapy used in combination with radiotherapy for head and neck squamous cell carcinoma (HNSCC). Gold nanoparticles (AuNPs) are expected to enhance radiotherapy effects in cancers. To investigate whether AuNPs combined with AG1478, an EI, enhanced irradiation effects on HNSCC cells, we first examined AG1478 adsorption on AuNP surfaces, using surface-enhanced Raman scattering, which indicated an adsorption equilibrium of AG1478 to AuNPs. We then used transmission electron microscopy to find internalization rates of AuNP alone and AuNP+AG1478; we found that intracellular uptake of AuNP alone and AuNP+AG1478 did not significantly differ. We compared cell numbers, proliferation, apoptosis, and migration between control cells and those treated with or without 60 nm AuNP (1.0 nM), AG1478 (0.5 μM), and irradiation (4 Gy). We found that AuNP+AG1478 inhibited proliferation more than AG1478 alone; the combination of irradiation+AuNP+AG1478 significantly reduced total cell numbers compared with the combination of irradiation+AuNP; AuNP+AG1478 increased apoptotic reaction to irradiation; the combinations of AuNP+AG1478 and irradiation+AuNP induced more apoptosis than AG1478+irradiation. Whereas AuNP+AG1478 enhanced cytotoxicity in human HNSCC cells by inhibiting proliferation, irradiation+AuNP enhanced cytotoxicity by inducing apoptosis.